"Who Are We Writing For?" - Sverker Lindblad; Daniel Pettersson (Universidade de Lisboa, 2023)
This study is based on an interest in interaction between science and society and how this structures science and society in tandem. In order to capture such interaction, we are analysing statements in scientific publications. The purpose of this study is to analyse relevancing in scientific publications by studying who are addressed by the research contributions and why these are considered to be relevant. Our case is the field of research labelled as International Large-Scale Assessments (ILSA), such as the OECD's Programme for International Student Assessment (PISA), created to analyse relations between educational designs and student performances. We identified a large set of research publications by means of the search engines Web of Science and Scopus. We selected publications that were peer reviewed and based on empirical comparisons between at least two countries. A large majority were only analysing student achievement, and few were researching impacts of educational variations. Relevance statements were mostly addressing policymakers. These findings are indicating strong social structuring of much ILSA research.